Diversity of Stingless Bee Species and Their Pests in the Village of Rarung, Central Lombok - Jihadi, Amrul; Supeno, Bambang; Sarjan, Muhammad; Haryanto, Hery; Pranggawan Azhari, Anjar (Jurnal Biologi Tropis, 2025)
The bekeeping of stingless bees is gaining popularity and developing in West Nusa Tenggara, as it provides an alternative livelihood and plays a vital role in the ecosystem through pollination. Despite growing public interest, detailed data on the diversity of stingless bee species and the challenges farmers face, particularly pest and disease infestations, remain scarce in some areas, such as Central Lombok. The aim of this study was to identify the bred species of stingless bees and the pest and disease species found in bee colonies in Rarung Village. The research was conducted from Juni to September 2024. The research methodology included field surveys, interviews with 4 farmers using snowball sampling techniques. In each farmers, we collected stingless bee and their pests from 10 stup and preserved in alcohol 70%. Morphological identification of bee species and pests was done in Plant Protection Laboratory, University of Mataram . The results showed that four species of stingless bees were being bred in Rarung Village: Tetragonula laeviceps, Tetragonula biroi, Tetragonula clypearis, and Tetragonula sapiens. Other major identified pests included ants (Formicidae), geckos (Gekkonidae), wasps (Vespidae), and signs of fungal pathogens. The results of this study show that bee species from outside Lombok were found in Rarung village that indicate thespecies diversity was affected by the practice of introducing species from outside Lombok.